How young people adapt to living with eczema. (2nd January 2020) - Ghio, D.; Muller, I.; Greenwell, K.; Roberts, A.; McNiven, A.; Langan, S.M.; Santer, M.
Summary: Eczema is a common skin condition, affecting about one in five children and one in 10 adults. This study, from the U.K., aimed to find out what it is like for young people in their late teens and early 20s to have eczema. The authors spoke to 23 young people to find out more. These interviews were transcribed (typed up) and analysed to find patterns. Young people with eczema described it as an episodic long‐term condition, or something that 'comes and goes' throughout their lives.  This made it challenging for them to look after their skin because it was hard to know what was making eczema worse or better. This may also have led to young people taking longer to shift from the mindset that they were seeking a 'cure' for their eczema to instead finding ways to control or manage their eczema.  Young people with eczema seemed to be lacking information about the disease, possibly because understanding of treatments were often based on advice passed on from their parents rather than directly from healthcare providers.  The episodic nature of eczema also challenged how people mentally adapted to the condition because they had often been told, including by healthcare providers, that they would 'grow out of eczema', yet their experience was that it hadn't gone away, or had gone away but kept returning.  The authors concluded that it may be better for healthcare providers to help people understand that eczema can follow a long‐term episodic (coming and going) course because where information provided does not match a person's experience, this can decrease trust in healthcare. Furthermore, young people with eczema need relatable, evidence‐based information to help them manage their condition effectively. This summary relates to the study: ?It's like the bad guy in a movie who just doesn't die': a qualitative exploration of young people's adaptation to eczema and implications for self‐care Abstract : Linked Article:  Ghio et al. Br J Dermatol 2020; 182 :112–118